Installation des jeunes agriculteurs et pluriactivité au Costa Rica - Parquet, Mathilde; Le Coq, Jean-François (EDP Sciences, 2017)
Small-scale family agriculture has been encouraged for several years by international institutions as an answer to global issues (food security and climate change), especially in Southern countries where this type of agriculture still prevails. One group of key actors is still poorly analyzed in agricultural studies: the young farmers. Yet they are potential innovators, they insure the generational renewal and thus maintain family agriculture. This paper studies the settling process of young farmers in two communities in Costa Rica resulting from land reforms. We show an important social change with the development of part-time farming activity. Three types of settling are identified: the taking over, the resumption and the creation of a new farm. Whereas resumption and creation trigger changes in the farm and in agriculture, taking over, the most common case, does not give rise to change. Territory characteristics, different capital endowment and the relationship to the former farm owner, who is often the father, can explain these different types of settlings. Our analysis highlights the necessity to consider the diversity of settling processes to promote adapted policy aiming at facilitating the generational renewal in family agriculture.